Gas exchange and yield of grafted yellow passion fruit under salt stress and plastic mulching - Antônio G. de L. Souto; Lourival F. Cavalcante; Edinete N. de Melo; Ítalo H. L. Cavalcante; Carlos J. A. Oliveira; Roberto Í. L. da Silva; Evandro F. de Mesquita; Rejane M. N. Mendonça (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Irrigation with saline water is one of the main factors that limit gas exchange and yield of yellow passion fruit in the semi-arid region of Brazil. The use of wild species of Passiflora ssp. tolerant to salinity as a rootstock and the application of mulching with plastic film can attenuate the effects of salt stress. The objective of present study was to evaluate the application of plastic film mulching and irrigation with saline water on the gas exchange and yield of yellow passion fruit grafted on P. cincinnata. The experiment was carried out under field conditions, from September 2019 to February 2021, in a 2 × (2 × 2) factorial scheme, in randomized blocks, in split plots and four replications. The treatments were related to irrigation with low-salinity (0.5 dS m-1) and high-salinity (4.5 dS m-1) water in yellow passion fruit plants, accession ‘Guinezinho’, propagated by seed and grafted on Passiflora cincinnata in the soil without and with plastic mulching. Irrigation with 4.5 dS m-1 water reduced gas exchange and yield of yellow passion fruit, but did not affect plants in the plastic mulched soil. Yellow passion fruit grafted on P. cincinnata showed increases in CO2 assimilation rate, but it was not reflected in fruit yield. For cultivation under high salinity conditions (4.5 dS m-1), it is recommended to use yellow passion fruit propagated by seeds in the soil with plastic film mulching.